Adversomics: a new paradigm for vaccine safety and design. (July 2015) - Whitaker, Jennifer A; Ovsyannikova, Inna G; Poland, Gregory A
<x xml:space="preserve">Abstract</x> Despite the enormous population benefits of routine vaccination, vaccine adverse events (AEs) and reactions, whether real or perceived, have posed one of the greatest barriers to vaccine acceptance – and thus to infectious disease prevention – worldwide. A truly integrated clinical, translational, and basic science approach is required to understand the mechanisms behind vaccine AEs, predict them, and then apply this knowledge to new vaccine design approaches that decrease, or avoid, these events. The term 'adversomics' was first introduced in 2009 and refers to the study of vaccine adverse reactions using immunogenomics and systems biology approaches. In this review, we present the current state of adversomics research, review known associations and mechanisms of vaccine AEs/reactions, and outline a plan for the further development of this emerging research field.